Adipose tissue autophagy related gene expression is associated with glucometabolic status in human obesity. (2nd January 2018) - Xu, Qing; Mariman, Edwin C. M.; Roumans, Nadia J. T.; Vink, Roel G.; Goossens, Gijs H.; Blaak, Ellen E.; Jocken, Johan W. E.
ABSTRACT: Adipose tissue autophagy (AT) is associated with human obesity and increased metabolic risk. Recent findings establish a role for autophagy in lipid metabolism. Here, we compared the expression of autophagy-related and lipolysis genes in human abdominal subcutaneous AT (SCAT) in overweight/obese subjects (n = 17) with or without impaired glucose tolerance in comparison with lean normal glucose tolerant individuals (n = 9), and investigated the association between AT autophagy and lipolysis. Human multipotent adipose-derived stem cells (hMADS) were used to investigate the effect of pharmacological HSL inhibition on changes in the autophagic flux. The expression of autophagy-related genes (ATG) 5, 7 and 12 in SCAT was significantly higher (p = 0.043, p = 0.015, p = 0.004, respectively) in overweight/obese compared to lean men, while expression of the classical lipases HSL (p = 0.092) and ATGL (p = 0.084) tended to be lower. ATG12 mRNA was positively correlated with BMI (r = 0.407, p = 0.039). ATG7 mRNA correlated positively with waist/hip ratio (WHR) (r = 0.420, p = 0.041), 2 h glucose concentration (r = 0.488, p = 0.011) and insulin (r = 0.419, p = 0.033). Multiple linear regressions revealed that ATG7 gene expression was positively related to 2 h glucose, independent of BMI, WHR and insulin. Gene expression interaction analysis showed that ATG7 mRNA negatively correlated with HSL (p<0.01) and ATGL mRNA expression (p<0.01). In line, treatment of differentiated hMADS with an HSL inhibitor increased LC3 accumulation, a marker of increased autophagic flux. Collectively, the present study demonstrated that a low expression of classical lipases in abdominal SCAT is accompanied by an increased expression of ATGs in overweight/obese subjects, which seems to be mainly related to glucose tolerance.